BIBLIOMETRIC ANALYSIS OF GLOBAL RESEARCH ON ISLAMIC MANAGEMENT USING SCOPUS DATABASE - Ghaliya Amur Ali Al Muqrashi; Asmuliadi Lubis; Mohd Abdul Wahab Fatoni bin Mohd Balwi (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to spread awareness of the importance of increasing scientific research in the field of Islamic management and help researchers and students of Islamic management well-known authors, institutions, and journals, as well as the volume of cooperation between countries with regard to publication. Clarifying the number of common citations and keywords used in Islamic management research. This study adopts a bibliometric method. In total, 280 articles and 59 reviews were retrieved from the Scopus database. This study analyzed the data using VOSviewer software. The analyses were divided into three main categories: co-citations with cited sources ,co-occurrence with author keywords, and co-authorship with the country. A total of 280 articles on Islamic management were published in the Scopus database from 1983 to 2020. Intellectual production is low, necessitating double efforts to enhance scientific publications in world-class journals. The Journal of Islamic Marketing is the top journal publishing Islamic management articles, and the most frequently used keyword is Islamic marketing, which ranked first among the countries with the highest scientific production , number of researchers, and universities of scientific production in the field of Islamic management. This study is a comprehensive review of academic articles on Islamic management using bibliometric analysis, which is rare in Islamic management. This is the first bibliometric study on Islamic management.